A Study on Inventory Management in Al Ain Hospital - Armoti, Ayman Al; Alkabi, Amal Salem (ExcelingTech, 2019)
The paper discusses each aspect about the inventory management that why there is this issue and what should be done to deal with this issue to make the inventory system that includes supply chain management more effective and advance. There are some issues in the warehouse itself that can be improved to solve this issue but this topic includes many topics to be shared and go to their details to know the depth of the issue and the reason behind this problem. The topics will cover the problems, the identification of the problems, the characteristics, the reasons, objectives, the solution, analysis of the problem and many more topics that includes some paragraphs of the discussion on the regarding issues. Then we discussed about survey that includes several questions that is related to the research topic to know what are employees point of view and how many of the employees are facing the same problem regarding this issue, this can be seen by the graphical results that we would prepare on excel through the questioner results.